Active resonator for low‐phase‐noise tunable oscillators. Issue 5 (May 2016) - Stornelli, Vincenzo; Pantoli, Leonardo; Leuzzi, Giorgio
ABSTRACT: In this article an active tunable resonator with high Q factor is described, for the design of a tunable low‐phase‐noise oscillator. The resonator is based on an active inductor with simple topology and high performance. In spite of the intrinsic noise inherent in the active inductor, the phase noise of the oscillator is limited by the high Q of the resonator. Frequency tuning range in the order of 5% is obtained without any optimization. Guidelines for the design of the active inductor and resonator are given, together with a practical example of voltage‐controlled oscillator. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1032–1035, 2016